Hubungan Pemberian Pekerjaan Rumah (PR) dengan Prestasi Belajar Mata Pelajaran Pendidikan Agama Islam Siswa SDN Kuanino Kecamatan Kota Raja Kota Kupang - Jihada, Ilfiana Iffah; Agusman (Ta lim Jurnal Pendidikan Agama Islam dan Manajemen Pendidikan Islam, 2022)
The purpose of this study was to determine the relationship between giving homework and PAI learning outcomes for students at SDN Kuanino, 2014/2015 academic year. The method in this research is correlational research. The sample used in this study was a saturated sample, that is, all the population studied were 26-1=25 students in grades III, IV and V at SDN Kuanino. Data collection techniques for variable X (Providing Homework) that is by using a questionnaire or questionnaire which is presented in the form of a statement consisting of 25 statements that have been tested through validity and reliability tests. To find out the significance of the relationship, a t-test was carried out, namely to get the results of rcount > rtable where ttable was at a significance level of 0.05 with dk (n-2) = (25-2) = 23 of 1.714, with test criteria Ho: rejected if tcount> ttable and Ho: accepted if tcount> ttable, because tcount = 4,943 > 1,714 rejected. Thus, it can be concluded that there is a significant relationship between giving homework and PAI learning outcomes for students at SDN Kuanino, Kupang City.